What drives CSR communication effectiveness on social media? A process-based theoretical framework and research agenda. Issue 3 (22nd April 2022) - Fernández, Paula; Hartmann, Patrick; Apaolaza, Vanessa
Abstract: While practice and research show that Corporate Social Responsibility (CSR) communication on social media can have positive effects on corporate reputation, brand attitude and purchase intention, consumer engagement with CSR posts has been underwhelming. Companies are not successfully tapping into the inherent potential of social media communication. This theoretical review integrates extant CSR and social media communication research to contribute to a better understanding of the processes involved in CSR effectiveness on social media. We develop a theoretical model of CSR social media communication, that takes into account its specific characteristics—sensitivity to peer influences through norm activation, interactivity, viral CSR message propagation through sharing, CSR empowerment, and humane-oriented appeals in CSR posts. The hypothesized framework connects CSR and social media-specific drivers with two social media CSR communication outcomes: i) CSR effectiveness in terms of CSR associations, corporate/brand attitude and purchase behavior, and ii) social media performance indicators related to propagation on the network—social media endorsement and opposition (liking, positive and negative commenting, and sharing of the CSR post). The model explains the resulting relationships through mediation processes based on CSR credibility and motive attribution, psychological consumer empowerment, moral emotions, as well as social identity and norm activation. Self-construal and community identification are identified as consumer-based contingency factors of these effects. The review framework provides an extended process-oriented agenda for future studies. The paper recommends multi-brand experimental field studies in a real-life social media setting and highlights the requirement of industry collaboration. The expected findings will help companies to choose relevant CSR initiatives, design effective CSR posts, boost viral propagation on the network, and counter and avoid social media opposition through negative feedback.